Pavilion of Judaism (Benjamin New Co., Ltd.)
Judaism maintained from ancient times by Jewish people all over the world is the main objective of the Pavilion of Judaism. On Ile Notre-Dame it is conveniently served by Minirail, by Metro Sainte-Helene and by the Expo-Express station on Ile Notre-Dame.